2018
DOI: 10.20944/preprints201803.0155.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Buckwheat and CVD Risk Markers, a Systematic Review and Meta-Analysis

Abstract: 15The effects of buckwheat intake on cardiovascular diseases (CVD) have not been systematically 16 investigated. The aim of the present study was to comprehensively summarise studies in humans and 17 animals evaluating the impact of buckwheat consumption on CVD risk markers and to conduct a meta-18 analysis of relevant data. Thirteen randomised, controlled human studies, two cross-sectional human 19 studies and twenty-one animal studies were identified. Using random effects models, the weighted 20 mean differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In human, buckwheat intervention significantly reduced glucose metabolism (0.85 mmol/L, 95% CI[1.31, 0.39]), total cholesterol (0.50 mmol/L, 95% CI [0.80, 0.20]) and triglycerides (0.25 mmol/L, 95% CI [0.49, 0.02]), compared with the control group. However, only triglycerides and total cholesterol showed slight differences in animals, with high heterogeneity [55]. On the other hand, another trial on quinoa suggested that quinoa consumption Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In human, buckwheat intervention significantly reduced glucose metabolism (0.85 mmol/L, 95% CI[1.31, 0.39]), total cholesterol (0.50 mmol/L, 95% CI [0.80, 0.20]) and triglycerides (0.25 mmol/L, 95% CI [0.49, 0.02]), compared with the control group. However, only triglycerides and total cholesterol showed slight differences in animals, with high heterogeneity [55]. On the other hand, another trial on quinoa suggested that quinoa consumption Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In a metaanalysis, Liangkui Li group investigated the effect of buckwheat on improving CVD risk factors in both human and animals. In human, compared with control group, the glucose metabolism, total cholesterol and triglycerides were significantly improved following buckwheat intervention [40]. However, in another trial regarding quinoa conducted by Liangkui Li group, they suggested that quinoa consumption can regulate glucose response, while only has minimal effects on other CVD risk biomarkers [41].…”
Section: Discussionmentioning
confidence: 96%